2002
DOI: 10.1002/ajh.10051
|View full text |Cite
|
Sign up to set email alerts
|

New α2 globin chain variant with low oxygen affinity affecting the N‐terminal residue and leading to N‐acetylation [Hb Lyon‐Bron α 1(NA1)Val→Ac‐Ala]

Abstract: Hemoglobin Lyon-Bron was found in two members of a family of German ascent presenting with a moderate normocytic anemia. In this alpha2 globin variant, the N-terminal valine of the chain was replaced by an alanine. Electrospray mass spectrometry of the a chain showed that, as normally, the initiator methionine was cleaved during globin processing but that the Na-terminal group was totally acetylated. This resulted in structural modi®cations of a region crucial for oxygen binding. As a consequence, hemoglobin L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Acetylation of the native protein, but not the recombinant one, may also contribute to the observed functional differences. Indeed Lacan et al (54) showed that a new ␣-chain variant, Hb LyonByron, is characterized by the replacement of the N-terminal valine by an alanine that is N-terminal acetylated. This resulted in a decreased oxygen affinity.…”
Section: Resultsmentioning
confidence: 99%
“…Acetylation of the native protein, but not the recombinant one, may also contribute to the observed functional differences. Indeed Lacan et al (54) showed that a new ␣-chain variant, Hb LyonByron, is characterized by the replacement of the N-terminal valine by an alanine that is N-terminal acetylated. This resulted in a decreased oxygen affinity.…”
Section: Resultsmentioning
confidence: 99%
“…Hb Niigata [β1Val → Leu, with complete retention of the initiator Met and 24% acetylation of the aminoterminal Met] is a new variant found in Japan (Ohba et al, 1997), and MS technology contributed to demonstrating the acetylation of the substituted Met at the N ‐terminal of its β‐subunit. Lacan et al (2002) showed total acetylation at the α‐subunit N ‐terminal substituted amino acid using ESI‐MS. We detected three different amino acids in β67 (Miyazaki et al, 1996; Kano et al, 2004), Val, Met, and Asp, in a case initially reported as Hb Bristol [β67Val → Asp], and found another case with this variant.…”
Section: Abnormal Hemoglobin (Hemoglobin Variant)mentioning
confidence: 99%